Efeito da aplicação tópica do gel contendo lipossomas com carvacrol sobre a nocicepção orofacial em camundongos - Oliveira, Adalúcia Correia de (2013)
Orofacial pain, although it is a problem that affects the quality of life of millions of people, is still poorly understood and, consequently, its treatment are difficult to predict. This treatment usually involves systemic pharmacotherapy, in most cases, it is accompanied by various side effects. Thus, the present study aimed to evaluate the pharmacological effect of topical application of a gel containing carvacrol on liposomes induced orofacial nociception in mice. First, we performed the test orofacial nociception induced by administration of 2% formalin into the upper lip of mice and then this tissue was removed for measuring the activity of myeloperoxidase (MPO). In the test described above, applying the carbopol gel (control group) or gel with liposomes containing carvacrol (1% and 5%) were performed 1 h before the induction of nociceptive orofacial; reference drug (diclofenac diethylammonium in gel form) was administered 2 hours before the induction of nociception. It was observed that at a concentration of 1%, the gel containing liposomes with carvacrol reduced the nociceptive behavior of scratching the orofacial region (34.4 ± 4.6 s, p <0.05) compared to the control group (74.1 s ± 4.6, p <0.05) is equivalent to the reduction observed in the group that was used reference drug (diclofenac diethylammonium gel - 34.0 ± 7.3 s, p <0.05). The gel 1% carvacrol was also able to reduce the activity of the enzyme MPO (0.7 ± 0.1 UMPO / mg tissue, p <0.05) compared to the control group (2.0 ± 0.3 UMPO / mg tissue, p <0.05) and behaved similarly to diclofenac diethylammonium group gel (0.5 ± 0.2 UMPO / mg tissue, p <0.05). Thus, it is concluded that the carvacrol gel containing liposomes at a concentration of 1% was effective in the control of nociception induced by formalin and had an important effect on cell migration at low concentrations suggesting that the gel containing liposomes has an effect carvacrol topic in the therapy of painful processes associated with orofacial region. However, such phenomena were not observed at 5% concentration.